Market integration of fresh milk in dairy business area of Pamijahan District and Cisarua District, Bogor Regency - Indonesia - Setianti, C.; Ekowati, T.; Setiadi, A. (Journal of the Indonesian Tropical Animal Agriculture, 2017)
The purpose of this study was to analyze the integration between dairy commodity market in milk distribution channels at Dairy Business Area, Pamijahan District and Cisarua District, Bogor Regency, West Java. The research method used was a survey method. Simple random sampling was a sampling technique used in this research to determine the respondent. Purposive method was a method that was used to determine research location. Respondents were 80 dairy cattle farmers at Dairy Business Area, Pamijahan District and 90 dairy cattle farmers at Cisarua District. Research data were consisted of primary data and secondary data. The results showed that the co-integration test in dairy farmers Dairy Business Area, Pamijahan District-Cisarua District trace statistic value of 18.27 was greater than 5% critical value of 15.41. The co-integration test in dairy cooperative level the trace statistic value of 28.63 was greater than 1% critical value of 20.04. Granger causality test results indicated that the results werea causality relation in Dairy Business Area, Pamijahan District and Cisarua District. There was an effect of the increase of milk price between Dairy Business Area, Pamijahan District and Cisarua District in Dairy Processing Industry Level, that’s mean there was an integration between the milk price in Dairy Processing Industry level.